Technological, economic and ecological aspects of selective coal mining from ultra-thin seams in conditions of Ukraine - Astafiev, D; Niedbalski, Z; Leschhorn, F; Tymoshenko, Ye (National Mining University, 2016)
Purpose. At present one of the topical problems associated with coal seams mining is the issue of induced wall-rock coal-cutting with stone, which results in coal getting clogged with refuse stone and turning into the rock mass. All mines of Western Donbas produce coal with average ash content of 31 – 49%. Selective mining can become a solu-tion to this problem as it allows to incorporate reserves with unconventional thickness that are in the mine balance sheet. The main objective of the present research is to substantiate selective technology of coal extraction applica-bility for mining of ultra thin coal seams in conditions of Ukrainian mines. Methods. Hazardous substances’ emissions into the atmosphere arising from implementation of bulk technology of coal extraction are estimated by analytical method. Findings. Consequences of the increase in power plants’ production capacity achieved by utilizing low-ash coal extracted by selective technology are presented. Originality. The research looks into economic efficiency of implementing selective extracting technology for mining reserves with unconventional thickness in Ukrainian mines, particularly in Western Donbas. Practical implications. The conducted analysis demonstrated that implementation of new technology will allow to resolve complex issues of coal quality increase, maintenance, reinforcement and reuse of mine workings, backfilling of worked-out area and improvement of ecological situation in coal mining regions.

Мета. В даний час однією з найбільш актуальних проблем при відпрацюванні вугільних пластів є питання про вимушене присікання бокових порід, внаслідок чого вугілля засмічується породою і перетворюється в гірничу масу. В середньому всі шахти Західного Донбасу видають на поверхню вугілля із зольністю 31 – 49%. Вирішенням цієї проблеми може бути перехід на селективне виймання, яке дозволить залучити некондиційні за потужністю запаси, що знаходяться на балансі шахти. Основною метою даної роботи є обґрунтування доцільності застосування селективної технології видобування вугілля для відпрацювання вельми тонких вугільних пластів в умовах шахт України. Методика. Проведена оцінка викидів шкідливих речовин в атмосферу від використання валової технології видобутку вугілля аналітичним способом. Результати. Наведені результати збільшення виробничої потужності електростанцій за рахунок використання низькозольного вугілля, видобутого при використанні селективної технології. Наукова новизна. Обґрунтована економічна ефективність впровадження селективної технології видобування для відпрацювання некондиційних вугільних запасів шахт України, зокрема Західного Донбасу. Практична значимість. Проведений аналіз показав, що впровадження нової технології дозволить комплексно вирішити питання підвищення якості вугілля, підтримки, кріплення й повторного використання виробок, закладки виробленого простору та поліпшити екологічну ситуацію у гірничодобувних регіонах.

Цель. В настоящее время одной из наиболее актуальных проблем при отработке угольных пластов является вопрос о вынужденной присечке боковых пород, вследствие чего уголь засоряется породой и превращается в горную массу. В среднем все шахты Западного Донбасса выдают на поверхность уголь с зольностью 31 – 49%. Решением этой проблемы может быть переход на селективную выемку, которая позволит вовлечь некондиционные по мощности запасы, находящиеся на балансе шахты. Основной целью данной работы является обоснование целесообразности применения селективной технологии добычи угля для отработки весьма тонких угольных пластов в условиях шахт Украины. Методика. Произведена оценка выбросов вредных веществ в атмосферу от использования валовой технологии добычи угля аналитическим способом. Результаты. Приведены результаты увеличения производственной мощности электростанций за счет использования низкозольного угля, добытого при использовании селективной технологии. Научная новизна. Обоснована экономическая эффективность внедрения селективной технологии добычи для отработки некондиционных угольных запасов шахт Украины, в частности Западного Донбасса. Практическая значимость. Проведенный анализ показал, что внедрение новой технологии позволит комплексно решить вопросы повышения качества угля, поддержания, крепления и повторного использования выработок, закладки выработанного пространства и улучшить экологическую ситуацию в горнодобывающих регионах.
Технологічні, економічні та екологічні аспекти селективного видобування вугілля з надтонких пластів в умовах України
The authors express their special gratitude to the Ministry of Science and Education of Ukraine; “Polish Erasmus for Ukraine” Program; Faculty of Mining and Geomechanics, Department of Geomechanics, Civil Engineering and Geotechnics of AGH of University of Science and Technology; Munich Mining & Industry Consulting GmbH.
Keywords: selective technology of coal extraction, waste-disposal dump, harmful substances emission, worked-out area, coal heat combustion, coal beneficiation, economic effect; селективна технологія видобутку вугілля, породний відвал, викид шкідливих речовин, вироблений простір, те-плота згорання вугілля, збагачення вугілля, економічний ефект; селективная технология добычи угля, породный отвал, выброс вредных веществ, выработанное пространство, теплота сгорания угля, обогащение угля, экономический эффект; Research Subject Categories::NATURAL SCIENCES::Earth sciences